Robot-assisted laparoscopic prostatectomy: a costs and break-even point analysis for decision-making in a university hospital and a regional healthcare system in Northern Italy (Epidemiology, Biostatistics, and Public Health, 2022)
BACKGROUND: Robotic Assisted Radical Prostatectomy (RALP) is one of the most expensive urological innovations. Prices of the “Da Vinci System” range from € 761.105 to € 1.902.762 for each unit, without taking into account the cost of maintenance and the use of additional devices. We evaluated outcomes, and costs retrospectively, comparing RALP to open retro-pubic radical prostatectomy (RRP) performed in our hospital between December 2009 and December 2010.METHODS: We compared 53 RALP, and 50 RRP in terms of costs, and clinical outcomes. We also implemented a Break Even Analysis in order to evaluate if the public reimbursement covered the total cost of RALP.RESULTS: According to our analysis, RALP showed lower hospitalization (p < 0,0001), higher early continence rate  (p < 0,0001), better potency rate in nerve sparing procedures  (p < 0,0142), and required no transfusions. Excluding the cost of purchasing and maintenance, single case costs were € 6.046,08 for RALP and € 4.834,11 for RRP, respectively. Considering the affordability of the technology, the point where the total revenue is sufficient to cover the total costs is an average of 60 cases performed per year, only in presence of additional reimbursement.CONCLUSIONS: Although our clinical analysis shows better results in favour of RALP, the economical analysis shows that RALP's costs are consistently higher than RRP. Considering also the purchasing costs, we demonstrate that the health gain of the technology does not necessarily offset the higher costs, even in a large, university hospital (1.000 beds).